Stock Price Booms and Expected Capital Gains - Klaus Adam; Johannes Beutel; Albert Marcet (University of Mannheim, Department of Economics, 2014)
The booms and busts in U.S. stock prices over the post-war period can to a large extent be explained by fluctuations in investors' subjective capital gains expectations. Survey measures of these expectations display excessive optimism at market peaks and excessive pessimism at market throughs. Formally incorporating subjective price beliefs into an otherwise standard asset pricing model with utility maximizing investors, we show how subjective belief dynamics can temporarily delink stock prices from their fundamental value and give rise to asset price booms that ultimately result in a price bust. The model successfully replicates (1) the volatility of stock prices and (2) the positive correlation between the price dividend ratio and expected returns observed in survey data. We show that models imposing objective or 'rational' price expectations cannot simultaneously account for both facts. Our findings imply that large parts of U.S. stock price fluctuations are not due to standard fundamental forces, instead result from self-reinforcing belief dynamics triggered by these fundamentals.
urn:nbn:de:bsz:180-madoc-361760
Keywords: G12; D84; 330